Pengaruh Pendidikan Kesehatan Pemeriksaan Payudara Sendiri (SADARI) Terhadap Perilaku Kader Dalam Mendeteksi Kanker Payudara Di Wilayah Kerja Puskesmas Tamangapa Kota Makassar - Abeng, Andi Tenri; Jama, Fatma (UI Scholars Hub, 2024)
Background. The most common cancer cases in Indonesia are breast cancer, namely 58,256 cases or 16.7% of the total 348,809 cases cancer. One of the causes is the delay for sufferers in independently detecting lumps early. Carrying out BSE will help the early detection program for breast cancer, thereby providing a higher cure rate for cancer sufferers. Aim. To determine the effect of health education about BSE on the behavior of cadres in detecting breast cancer in the Tamangapa Health Center work area, Makassar City. Method. This study was a quasi-experimental study with a Pretest and Posttest Group Design. Respondents were 42 health cadres of the Tamangapa Health Center in Makassar City who were drawn using nonprobability sampling. Data collection using pre-test and post-test questionnaires regarding early detection of breast cancer. Data were analyzed using the Wilcoxon test and Paired Sample t Test. Result. There is an effect of health education about BSE on the behavior of cadres in detecting breast cancer. Health education interventions about BSE are considered effective in improving the behavior of cadres in detecting breast cancer in the work area of the Tamangapa Health Center in Makassar City.